The Impact of Integrating 3D-Printed Phantom Heads of Newborns with Cleft Lip and Palate into an Undergraduate Orthodontic Curriculum: A Comparison of Learning Outcomes and Student Perception - Sarah Bühling; Jakob Stuhlfelder; Hedi Xandt; Sara Eslami; Lukas Benedikt Seifert; Robert Sader; Stefan Kopp; Nicolas Plein; Babak Sayahpour (Dentistry Journal)
Background/Objectives: This prospective intervention study examined the learning effect of using 3D-printed phantom heads with cleft lip and palate (CLP) and upper jaw models with CLP and maxillary plates during a lecture for dental students in their fourth year at J. W. Goethe Frankfurt University. The primary aim was to evaluate the impact of 3D-printed models on students’ satisfaction levels along with their understanding and knowledge in dental education. Methods: Six life-sized phantom heads with removable mandibles (three with unilateral and three with bilateral CLP) were designed using ZBrush software (Pixologic Inc., Los Angeles, CA, USA) based on MRI images and printed with an Asiga Pro 4K 3D printer (Asiga, Sydney, Australia). Two groups of students (n = 81) participated in this study: the control (CTR) group (n = 39) attended a standard lecture on cleft lip and palate, while the intervention (INT) group (n = 42) participated in a hands-on seminar with the same theoretical content, supplemented by 3D-printed models. Before and after the session, students completed self-assessment questionnaires and a multiple-choice test to evaluate knowledge improvement. Data analysis was conducted using the chi-square test for individual questions and the Wilcoxon rank test for knowledge gain, with the significance level set at 0.05. Results: The study demonstrated a significant knowledge increase in both groups following the lecture (p < 0.001). Similarly, there were significant differences in students’ self-assessments before and after the session (p < 0.001). The knowledge gain in the INT group regarding the anatomical features of unilateral cleft lip and palate was significantly higher compared to that in the CTR group (p < 0.05). Conclusions: The results of this study demonstrate the measurable added value of using 3D-printed models in dental education, particularly in enhancing students’ understanding of the anatomy of cleft lip and palate.